2017
DOI: 10.1111/jep.12838
|View full text |Cite
|
Sign up to set email alerts
|

Variations in demand and provision for publicly funded outpatient musculoskeletal physiotherapy services across Quebec, Canada

Abstract: The variations in provision of physiotherapy services between regions reported in our study did not correspond to the variations in demand. Such geographic variations and demand to provision mismatches may create inequity in access to services, especially for those unable to afford private services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…That study concluded that variation in provision of physiotherapy service did not appear to be related to demand for care, but rather was driven by wait times and indicators of insufficient provision of service. 33 We also reported an inverse association of the availability of PTs and chiropractors with the tendency to prescribe opioids at the first SP visit. A cross-sectional study of younger (disabled) Medicare beneficiaries also reported that the per-capita supply of DCs and spending on chiropractic manipulative therapy were inversely correlated with the percentage of younger Medicare beneficiaries receiving at least one opioid as well as 6 or more opioid prescription fills.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…That study concluded that variation in provision of physiotherapy service did not appear to be related to demand for care, but rather was driven by wait times and indicators of insufficient provision of service. 33 We also reported an inverse association of the availability of PTs and chiropractors with the tendency to prescribe opioids at the first SP visit. A cross-sectional study of younger (disabled) Medicare beneficiaries also reported that the per-capita supply of DCs and spending on chiropractic manipulative therapy were inversely correlated with the percentage of younger Medicare beneficiaries receiving at least one opioid as well as 6 or more opioid prescription fills.…”
Section: Discussionmentioning
confidence: 64%
“…This is supported by findings in the province of Quebec, Canada of the use of early physiotherapy services. That study concluded that variation in provision of physiotherapy service did not appear to be related to demand for care, but rather was driven by wait times and indicators of insufficient provision of service 33 …”
Section: Discussionmentioning
confidence: 98%
“…Findings showed that the ETOs are concentrated in three Canadian provinces (Ontario, Québec, and British Columbia). Previous research has found variations in the density of rehabilitation professionals in different Canadian provinces, 64 with a greater density in areas with academic centers compared with rural and remote areas. [65][66][67][68] The concentration of ETOs in these three provinces seems to reflect the presence of larger numbers of rehabilitation professions and academic settings in those areas and provinces.…”
Section: Etos Characteristicsmentioning
confidence: 94%
“…Similarly, a study by Deslauriers, Raymond [ 19 ] found a mean waiting time of 7.6 months (range from 0 to 77 months) for outpatient physiotherapy services in publicly funded hospitals in the province of Quebec (Canada). This delay in access to external rehabilitation services is exacerbated by a persistent shortage of healthcare professionals and an increasing demand for services for an aging population [ 20 , 21 ]. With the goal of optimizing post-acute care physical functioning and functional independence among older adults admitted to acute care or their rehabilitation facilities, the MWIIUHSSC piloted the Post-Acute Home Physiotherapy Program (PAHP).…”
Section: Introductionmentioning
confidence: 99%